Dental implant treatment failures related to tobacco smoking - Szpak, Piotr; Szymańska, Jolanta; Koszuta, Agnieszka (Polish Journal of Public Health, 2012)
Tobacco smoking is one of the essential factors that may affect dental implant treatment. A great majority of studies on the relationship between smoking and dental implant failures indicate a clearly negative influence of the addiction, while only few papers do not report such a connection. Basing on the implantology literature data, the paper presents the criteria of success and failure in dental implant treatment. The influence of tobacco smoking on implant treatment failure, and especially on implant survival as the main criterion of therapeutic success, was described. The current status of knowledge on the effect of tobacco smoking on the crestal bone loss around implants was also presented. In addition, the paper describes in detail a possible pathomechanism of the influence of nicotinism on the crestal bone loss around implants as one of the factors leading to treatment failure. The necessity of a rational consensus, involving also the legal aspect of the problem, between a tobacco-smoking patient and a doctor providing implant treatment was emphasized.